Compliance of the Iraqis laws to the requires of the U.N agreement for the washing of money (Al-Mansour Journal, 2023)
The crime of washing money considered as one of the most dangerous crimes of this century , Its represent the challenge in front of the monetary establishment .In addition of its being a test for the ability of the legal principles for the realization of activating the criminal confrontation by fighting all of its new aspects . Hence , the importance of this crime is considered subservience of the criminal activity which brought charity revenues , therefore it was a must to cloth with legality these criminal revenues on what is known as (dirty money) in order to facilitate it use with the most ease …. So that it is considered as an exit to the dilemma because of the difficulty in dealing with their criminal activities , especially those which bring exorbitant money such as drug smuggling , weapons trafficking est.…. Where as , its requires a grate efforts by the international community of the international financial, bank of experts and non experts criminals to com together and cooperate that’s what made it one of the international crimes so its not easy to fight this kind of crimes whitout international cooperation